Trends and Challenges in Educational Equity Research under China's Double Reduction Policy: A Bibliometric Analysis - Qiuyan Zhang (International Journal of Education and Humanities, 2025)
Educational equity (EE), including China, has become a critical issue in global education policies. Implementing the "double reduction" (DR) policy poses significant challenges in ensuring equitable access to quality education while reducing students' academic burdens and regulating excessive supplementary education. This study aims to explore the critical trends in EE research within the framework of the DR policy using bibliometric methods. By employing CiteSpace software, this study conducts a visual analysis of 779 documents retrieved from the Peking University Core Journals and CSSCI databases. The analysis applies various bibliometric techniques, including author co-occurrence, institutional collaboration, keyword co-occurrence, and keyword clustering, to uncover the key themes and developmental trajectories of domestic research in this field. The findings reveal that the Department of Education has emerged as a central driver of EE research under the DR policy. Key research clusters focus on critical themes such as stakeholder competition, endogenous development, public educational services, academic achievement, and value dimensions. These clusters highlight the diverse and evolving nature of EE research in China. Based on these findings, this study recommends that future research should (1) deepen the evaluation and optimization of educational policies to enhance equity, (2) expand the scope of EE research by exploring new dimensions, particularly in the integration of digital technology, and (3) advance the understanding of how educational technology can support equitable access to educational services. These insights provide a foundation for addressing emerging challenges in pursuing educational equity